Monitoring the vaccination of pregnant women against pertussis - single-centre one-year study in the Czech Republic - Liptakova, Monika; Kostalova, Jana; Kyncl, Jan; Maly, Marek; Krizova, Marcela; Herman, Hynek; Fabianova, Katerina (Bratislavske lekarske listy, 2023)
OBJECTIVES: This observational study aimed to analyse data from big maternity hospital, determine the vaccination coverage and provide source information for further activities. BACKGROUND: Although vaccination of pregnant women against pertussis is recommended in the Czech Republic, data on vaccination coverage are not available. METHODS: The self-completed questionnaire was distributed to 5,475 pregnant women in the maternity hospital between 2020 and 2021. Questionnaires collected mother's sociodemographic characteristics, pertussis vaccination status and sources of recommendations for vaccinations during pregnancy. RESULTS: A total of 4,617 completed questionnaires were analysed. Pertussis vaccination coverage during pregnancy was 1.6 % (95% confidence interval, 1.3-2.0 %). Only 12.5 % of women knew about the possibility of being vaccinated against pertussis during pregnancy. Women considered pertussis vaccination in pregnancy as important (12.9 %), useful (49.1 %) and useless (24.0 %). Of 579 pregnant women who had information about pertussis vaccination during pregnancy, only 12.1 % were vaccinated, while among those who did not have this information, 0.1% were vaccinated during pregnancy (p < 0.001). The most frequent source of information was Internet, then a general practitioner. CONCLUSION: It is necessary to raise awareness of recommendations for pregnancy vaccination among public and professionals, to emphasize the benefits of such vaccination in order to increase the vaccination coverage (Tab. 3, Ref. 31). Text in PDF www.elis.sk Keywords: pertussis, whooping cough, pregnancy, vaccination, health knowledge, prevention.
Keywords: Pregnancy Complications, Infectious; Vaccination; Female; Whooping Cough; chřipka lidská; infekční komplikace v těhotenství; vakcinace; ženské pohlaví; Česká republika; Pregnancy; Humans; lidé; těhotné ženy; Pregnant People; Czech Republic; těhotenství; pertuse; Influenza, Human